Uterine artery pseudoaneurysm : A case of late intraabdominal haemorrhage after caesarean section - Soe, Lwin; Thidar, Soe; Myat, San Yi; Mui, Christine Fong Lee; Cheng, Sue Marie Kian Pei; Tin, Moe Nwe (Malaysian Medical Association, 2020)
Uterine artery pseudoaneurysm (UAP) is a rare acquired vascular malformation associated with vaginal bleeding or intraabdominal haemorrhage occurring after pelvic surgery. Pseudoaneurysm may present with delayed, severe haemorrhage after a seemingly uncomplicated initial postoperative period. Treatment is therefore necessary to prevent further complications. We describe here a case of a 32-year-old mother, who presented with abdominal pain and intraabdominal bleeding, 20 days after Caesarean Section. Computerised Tomography (CT) scan showed the presence of haemoperitoneum, suggestive of pseudoaneurysm at the right cervical artery which was successfully managed with emergency angiographic embolisation.